Um oásis no sertão? A educação profissional e o desenvolvimento do Seridó Potiguar - Gomes, Danilo Cortez (2020)
Considering that education is one of the indispensable means for the development of a region, it is understood that the expansion and interiorization of professional and technological education in Brazil has influenced the various corners of the country, among them, the Seridó Potiguar. Pacheco (2011) emphasizes that besides teaching itself, one of the purposes of professional education through the Federal Institutes, is to act in favor of local and regional development, which in fact is already emphasized in the diagnoses made by some political actors when elaborating local and regional development policies at the state level (CAPRIGLIONE, MORETTI and NOGUEIRA, 2017). In this context, this thesis starts from the following question: What is the relationship between professional education and state planning for the development of Seridó Potiguar? This question arises from the understanding that IFRN contributes positively to the development of Seridó Potiguar, however, not always with full convergence with the objectives and purposes of local and regional development policies of state planning, represented here by the Project RN Sustainable. Therefore, our hypothesis is that these apparent partners (IFRN and RN Government) have different understandings about local development: the Federal Institute seeks to promote what is universal in this reality while state planning continues to identify only so-called “natural vocations” or potentialities of the region. Thus, the general objective of this study was to examine the relationship between the expansion and interiorization of professional and technological education and the development of Seridó Potiguar, based on the activities developed by IFRN and the actions defined in state development planning through the Project RN Sustainable. Consequently, the specific objectives were: 1) to investigate the process of interiorization of IFRN, more specifically in Seridó Potiguar; 2) to analyze the actions and specificities of the Project RN Sustainable for Seridó Potiguar; 3) to examine the relationship between IFRN activities in Seridó Potiguar and local development planning advocated in state planning guided by the Project RN Sustainable; and 4) to examine the convergences and divergences between IFRN's proposal for professional and technological education for Seridó Potiguar in relation to the proposals of the Project RN Sustainable for the same region in the areas of local development and professional education. As for the methodological construct, this research starts from the interpretative paradigm, of qualitative nature. About the objectives of the study, the research is explanatory; and as for the procedures, it is characterized by a documental and field research. Regarding the treatment and analysis of data, the content analysis proposed by Bardin (2009) was used. The results confirmed the hypothesis when they revealed that there are more divergences than convergences in the relationship between IFRN and state development planning, that is, the partnership between the Government of the RN and the IFRN is not fully effective, however, the data corroborate the importance of IFRN in the development process of Seridó Potiguar.